Метод динамического баланса в газотранспортных системах - Набатова, С. Н.; Мамедова, А. А. (ХНУРЭ, 2008)
In the given work the method of dynamic balance which allows not only to diagnose a condition of a mode of transport of natural gas on a gas pipeline is considered, and to define infringement of balance of natural gas in GTS. It is received possibilities of the control of dynamic balance of natural gas in real time, that allows to diagnose a condition of a mode of system and also to reveal and estimate size of nonproductive losses and criminal selections of natural gas on fragments GTS
Keywords: баланс в газотранспортных системах; газотранспортная система